PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN PROMOSI PENJUALAN TERHADAP MINAT BELI PADA SHOPEE FOOD DI SIDOARJO - Ratna Lailatul As’ari; Satrio Sudarso; Dewi Komala Sari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to explore the influence of service quality, price perception, and sales promotion on consumer purchasing interest in shopee food, especially in Sidoarjo. With the rapid development of e-commerce and food delivery services, understanding the factors that influence consumer purchasing decisions is very important for companies to maintain competitiveness in the market. This study uses a quantitative descriptive approach with non-probability sampling, targeting 100 respondents who have used shopee food. Data were collected through online questionnaires and analyzed using multiple linear regression analysis. The results showed that all variables, namely service quality, price perception, and sales promotion, have a significant influence on consumer purchasing interest. This study determines the importance of these factors in shaping consumer behavior and provides insight for businesses to formulate better marketing strategies.